Rejuvenating Sustainable Mangrove Ecotourism Destinations Using a Tetrapreneur Model: A Case of Kulon Progo, Indonesia - Aji, Khusnul Bayu; Fatimah, P.L. Rika (Journal of Indonesian Tourism, Hospitality and Recreation, 2024)
ABSTRACTThis article aims to investigate actual conditions and construct potential recommendations to rejuvenate mangrove ecotourism destinations to be more sustainable along the southern coast of Kulon Progo using a Tetrapreneur Model. In this study, a qualitative research approach was adopted. To obtain primary data, systematic observation and in-depth interviews were utilized, while a literature study strategy involving a comprehensive review of relevant documents in various forms, such as textual, visual, digital, and physical items, was employed to collect secondary data. The results indicate that the four approaches of the Tetrapreneur Model, namely Chainpreneur, Marketpreneur, Qualitypreneur, and Brandpreneur, as examined in this study, have their own unique set of facts, comprising Improvement Gap Facts, Sustainability Potential Facts, and Supporting Facts for the rejuvenation of mangrove ecotourism destinations. Furthermore, stakeholders in mangrove ecotourism destinations, particularly local community groups acting as tourism business operators and the local government of Jangkaran Village, are suggested to consider implementing several practical recommendations based on the Tetrapreneur Model.ABSTRAKTujuan dari artikel ini adalah untuk menginvestigasi kondisi aktual dan mengkonstruksi rekomendasi potensial untuk meremajakan destinasi ekowisata mangrove agar lebih berkelanjutan di sepanjang pesisir selatan Kabupaten Kulon Progo menggunakan Model Tetrapreneur. Kajian ini mengadopsi pendekatan penelitian kualitatif. Untuk mengumpulkan data primer, observasi secara sitematis dan wawancara mendalam digunakan, sedangkan studi literatur yang melibatkan tinjaun komprehensif terhadap dokumen-dokumen yang relevan dalam berbagai bentuk, mulai tekstual, visual, digital, hingga fisik digunakan untuk mengumpulkan data sekunder. Hasil menunjukkan bahwa empat pendekatan dari Model Tetrapreneur, yakni Chainpreneur, Marketpreneur, Qualitypreneur, dan Brandpreneur, seperti yang dikaji dalam tulisan ini, memiliki fakta-fakta uniknya masing-masing, terdiri dari Fakta Gap Perbaikan, Fakta Potensi Keberlanjutan, dan Fakta Pendukung dalam konteks peremajaan destinasi ekowisata mangrove. Selanjutnya, para pemangku kepentingan di destinasi ekowisata mangrove, khususnya komunitas lokal sebagai pengelola bisnis pariwisata dan pemerintah Desa Jangkaran, disarankan untuk mempertimbangkan penerapan beberapa rekomendasi praktis berdasarkan Model Tetrapreneur.